PENERAPAN MODEL NUMBER HEAD TOGETHER UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SD NEGERI 1 PEUKAN PIDIE - Nasri Diana; Dara Ulfa Harahap (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2024)
This study aims to improve student learning outcomes by using the Number Head Together model in 4th grade of SD Negeri 1 Peukan Pidie. This type of research is classroom action research conducted in 3 cycles. The research subjects were grade IV students, totaling 42 students consisting of 19 boys and 23 girls. Data collection uses the Field Research method with observation and test techniques. Data analysis was carried out qualitatively and quantitatively. Learning outcomes have increased with the acquisition of student scores in the first cycle with an average value of 63.1 with 15 students completing with a percentage of 36%, in the second cycle the average value obtained by students is 68.4 with 22 students completing students with a percentage of 52%, in cycle III the average value obtained by students is 84 with 42 students who complete with a complete percentage of 100%.